Fight Fungi with Fungi: Antifungal Properties of the Amphibian Mycobiome - Kearns, Patrick J.; Fischer, Sarah; Fernández-Beaskoetxea, Saioa; Gabor, Caitlin R.; Bosch, Jaime; Bowen, Jennifer L.; Tlusty, Michael F.; Woodhams, Douglas C. (Frontiers in Microbiology, 2017)
Emerging infectious diseases caused by fungal taxa are increasing and are placing a substantial burden on economies and ecosystems worldwide. Of the emerging fungal diseases, chytridomycosis caused by the fungus Batrachochytrium dendrobatidis (hereafter Bd) is linked to global amphibian declines. Amphibians have innate immunity, as well as additional resistance through cutaneous microbial communities, and the development of probiotic bacterial therapies that have had mixed results, yet the the role of fungi in the protection against Bd infection in unknown.. We used a four-part approach to examine the overlapping roles of bacterial and fungal microbiota in pathogen defense with a combination of high-throughput sequencing and culturing of symbiotic fungi from poison arrow frogs (Dendrobates sp.). Our results revealed that cutaneous fungal taxa differed from environmental microbiota across three species and a subspecies of Dendrobates spp. frogs. Cultivation of host-associated and environmental fungi reealved numerous taxa with the ability to inhibit or enhance the growth of Bd. The abundance of cutaneous fungi contributed more to Bd defense (~45% of the fungal community), than bacteria (~10%) and that frog species harbored distinct inhibitory communties from the environment.Further, we demonstrated that a fungal probiotic therapy did not induce an endocrine-immune reaction, in contrast to bacterial probiotics that stressed amphibian hosts and suppressed antimicrobial peptide responses, limiting their long-term colonization potential. Our results suggest that probiotic strategies against amphibian fungal pathogens should, in addition to bacterial probiotics, focus on host-associated and environmental fungi such as Penicillium and members of the families Chaetomiaceae and Lasiosphaeriaceae.